If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2(-7x + 21) = 0 Reorder the terms: 7x + 2(21 + -7x) = 0 7x + (21 * 2 + -7x * 2) = 0 7x + (42 + -14x) = 0 Reorder the terms: 42 + 7x + -14x = 0 Combine like terms: 7x + -14x = -7x 42 + -7x = 0 Solving 42 + -7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -7x = 0 + -42 Combine like terms: 42 + -42 = 0 0 + -7x = 0 + -42 -7x = 0 + -42 Combine like terms: 0 + -42 = -42 -7x = -42 Divide each side by '-7'. x = 6 Simplifying x = 6
| 5*m=13 | | -2s+5=11-4s | | 6h+12+12h-6= | | -6+2n=3n-6t-13 | | 3y-4x=-12 | | 2t+3=8 | | -3+3y=-y+13 | | 3v+9=8v-16 | | 6x-4(7x-14)=232 | | 5x^2-90=10+4x^2 | | -16x^2+150x+120=0 | | 27+4x=49 | | 3(2x-5)=(5x-4)+5 | | -14+2=-8 | | x+9y=92 | | 5.25x+3.25=9.6+3.2 | | 17=0.5h-2 | | 5+6(6x+5)=-181 | | 5x-2y+4x-2y= | | 3(2x-5)=5x-4+5 | | 5.26=m-6 | | 6y=3+2x | | 3(5x+3)=8x+15+7x-6 | | .75n-18=2.75n-4 | | 0.6x+2=-10 | | 7*x-14=5*x+10 | | 4z-36=-12 | | 72+(-9f)=-18f | | 6n+7-2n-14=3y-6 | | 6y+8=26 | | -4x+6(-7x-7)=188 | | -x-2y-8x-2y=a |